PENGARUH KONFLIK KERJA, KELELAHAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PT USAHA KARYA CILACAP - Dewi, Sandra; Darmawan, Akhmad; Muji R., Tri Septin; Haryanto, Totok (Jurnal Akuntansi dan Pajak, 2024)
The aim of this research is to determine the effect of work conflict, work fatigue and workload on employee performance. This type of research is quantitative survey research. The population of this study was 120 employees and the sample size was 107. The sampling technique used was nonprobability sampling with a sample method, namely purposive sampling. The analysis test used multiple regression using SPSS version 20 for Windows software. The research results show that work conflict has a negative and significant effect on employee performance. Work fatigue has a negative and insignificant effect on employee performance. Workload has a negative and significant effect on employee performance